EVALUATION OF THE ROLE OF THE (KEUJRUEN BLANG HOP) IN REGION IV MANGGENG DISTRICT SOUTHWEST ACEH DISTRICT - Marwalis; Dedy Darmansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The purpose of this study was to evaluate the role of the Keujrun Blang Hop in Manggeng District in region IV. This research was conducted in December 2022. The research location was carried out in Manggeng District, Region IV to be precise, namely the villages of Lhok Puntoi, Ladang Panah, Pusu ingn jaya and Seunelhop. The sampling method used was accidental random sampling, namely a sampling method or technique in which random sampling was taken. In this study, the population totaled 489 people by calculating the sample size which was carried out using the Slovin Formula with the allowance used was 14% so that there were 47 sample people. This research method uses a Likert Scale and IPA (Importance Performance Analysis) analysis where through this method researchers can determine the level of farmer satisfaction based on the assessment of the attributes. The results showed that there was a stain between farmers' expectations (importance) and the service (performance) provided by Hop Keujrun to rice farmers. which is shown in P8 and P14 where the expected value (performance) is smaller than the service (importance). Based on the results of the IPA Cartesian diagram, the attributes of the role of Hop Keujrun blang in region IV have been said to be satisfactory because there is nothing that needs to be improved which is shown in Quadrant I.